A silent voice / vol. 6 - Ōima, Yoshitoki; LeCroy, Steven (2015)
Time stands still for both Shoya and Shoko. Triggered by past traumas, Shoya coldly attacked his friends and burnt the bridges he first set out to rebuild. Shoko feels a deep responsibility for this disaster and attempts to pay for it by taking her own life. Meanwhile, each of their friends finally show their true colors. After everything has fallen apart, how will they mend their hearts and put the pieces back together?
Reads from right to left.
"A Kodansha Comics Trade Paperback Original"--Colophon.
"T, ages 13+"--Back cover.
Translation of: Koe no katachi.
Keywords: Deaf people -- Fiction; People with disabilities -- Fiction; Bullies and bullying -- Fiction; Conduct of life -- Fiction; Schools -- Fiction; Graphic novels; Deaf children; Bullying; Conduct of life; School children; Teenagers; Comic books, strips, etc; Graphic novels